THE TABOO OF PRECEDING SISTER IN MARRY: A MINANGKABAU SOCIO CULTURE ANALYSIS - Shafra Shafra; Yulia Rahmi (State Institute of Islamic Studies Batusangkar, 2021)
Ideally in the family, the order of marriage starts from the eldest child. Then followed by the second child, the third child and so on. But the reality is different. There are many cases that the youngest child preceded the older brother or sister in marry. In many areas, stepping over older siblings in marriage is commonplace. It doesn't matter whether the one who gets married is a man or woman. However, in Tabu Baraie Nagari Paninjauan Tanah Datar, stepping over an older siblings in marriage is taboo, in particular an older sister. It is forbidden for a sister or brother to step over her/his older sister in marriage. Generally, the older sister who is stepped on by her sister's marriage, her life is single. The aims of this study was to determine the origin of the taboo to step over the marriage of older sisters in a sociological study.Keywords: marriage, stepping over the marriage, older sister.